2014
DOI: 10.1111/jace.13325
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor Ferroelectric BaTiO3–Bi(Mg2/3Nb1/3)O3 Ceramics for Energy Storage Application

Abstract: Perovskite solid solution ceramics of (1 − x)BaTiO3–xBi(Mg2/3Nb1/3)O3 (BT–BMN) (x = 0.05–0.2) were synthesized by solid‐state reaction technique. The results show that the BMN addition could lower the sintering temperature of BT‐based ceramics. X‐ray diffraction results reveal a pure perovskite structure for all studied samples. Dielectric measurements exhibit a relaxor‐like characteristic for the BT–BMN ceramics, where broadened phase transition peaks change to a temperature‐stable permittivity plateau (from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
188
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 480 publications
(196 citation statements)
references
References 58 publications
3
188
1
4
Order By: Relevance
“…4 and 6, which could be regarded as the desorption event; susceptibility should increase with temperature due to the nature of the material, there are no ferroelectric transitions to cause decrease in the real part of the susceptibility. [20][21][22]25 The number of relaxations that can be observed in wet sample is larger than the dried sample. As discussed previously, at high temperatures close to 300 C, the data for the wet and dried sample are converging to each other indicating the similarities in both responses and confirm that the initial measurement in the first ramp is a dry-bake cycle.…”
Section: Dielectric Relaxationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and 6, which could be regarded as the desorption event; susceptibility should increase with temperature due to the nature of the material, there are no ferroelectric transitions to cause decrease in the real part of the susceptibility. [20][21][22]25 The number of relaxations that can be observed in wet sample is larger than the dried sample. As discussed previously, at high temperatures close to 300 C, the data for the wet and dried sample are converging to each other indicating the similarities in both responses and confirm that the initial measurement in the first ramp is a dry-bake cycle.…”
Section: Dielectric Relaxationsmentioning
confidence: 99%
“…The method has been applied to various different material systems. [7][8][9][10][11][20][21][22] Electrical properties of materials can be determined from the impedance measurements by performing current measurements with applied voltage and using the geometrical capacitance C 0 , the geometry of the sample. For example, for the complex permittivity, " Ã is estimated from the current measurement as a complex capacitance C Ã for a given geometrical shape of the measurement electrodes, which determine the geometrical capacitance C 0 , Here, the angular frequency, !, independent material properties are of relative permittivity at high frequencies, " 1 , and Ohmic (direct-current) conductivity, 0 ; ı ¼ ffiffiffiffiffiffi ffi À1 p .…”
Section: Introductionmentioning
confidence: 99%
“…So, there are two possible routes to improve the energy-storage density of AFE and FE ceramics for energy storage applications: One is to enhance the BDS for high E and another is to increase the limit of integration by enlarging the difference between the P max and P r . For the first route, it was found that AFE ceramic ( [17][18][19][20][21] It indicated that partial occupancy of Bi 3þ at the A site of the perovskite compound could effectively improve the energy storage properties. As a promising candidate system, relaxor ferroelectrics BaTiO 3 (BT)-based ceramics play a key role in the area of energy density capacitors because of their low P max , high P r , and low loss.…”
mentioning
confidence: 99%
“…Wang et al, examined the solid solution, (1-x)BaTiO3-xBi(Mg2/3Nb1/3)O3, reporting basic dielectric properties and energy storage capabilities [42]. Composition x = 0.2 exhibited temperature-stable dielectric response with r varying from 628-787 in the temperature range -50 to +300ºC: tan ≤ 0.025 over the temperature range 0-150ºC (estimated).…”
Section: Batio3-bi(mg2/3nb1/3)o3mentioning
confidence: 99%